Matthew - Evans, Craig A. 1952- (Cambridge University Press, 2012)
This book is a verse-by-verse analysis of the New Testament Gospel of Matthew. It provides a comprehensive introduction to the Gospel, which describes the world of Jesus and his first followers. This commentary explores the historical, social and religious contexts of Matthew and examines the customs, beliefs and ideas that inform the text. Unfamiliar to many readers of the New Testament, this background will help readers fully understand the text of Matthew, which focuses on what Jesus taught and why the religious authorities in Jerusalem rejected his message and gave him up to the Roman governor for execution. This book will be an important tool for the clergy, scholars and other interested readers of Matthew
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible / Matthew / Commentaries; Bibel -- Matthäusevangelium; Bibel; Kommentar